PENGARUH PERSPEKTIF FRAUD TRIANGLE TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Putu Mutiari; I Ketut Parnata; AA Putri Suardani (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The purpose of this study is to know the influence of fraud triangle perspective that developed to financial statement fraud. This study used three independent variables, financial stability that measured by change in total assets ratio (ACHANGE), ineffective monitoring measured by independent commissioner ratio (IND), change in auditors (AUDCHANGE) measured by dummy variable. Financial statement fraud that measured by discretionary accruals. The population in this research is banking company that listed in Indonesia Stock Exchange during the period 2013-2015. Based on criteria of sampling, gets 35 banking companies as observation unit. The type of data used are secondary data, in the form of annual reports of banking companies listed on Indonesia Stock Exchange during the period 2013-2015. Based on t-test in this study shows that the t-value of financial stability pressure is -3.778 with significance of 0.000, t-value of ineffective monitoring is -0.498 with significance of 0.619, tvalue of change in auditors is -0.671 with significance of 0.504